Analisis Kemampuan Argumentasi Ilmiah Peserta Didik Menggunakan Pola Toulmin Pada Materi Perubahan Lingkungan Di SMA/MA - Hapid, Shakila Melody; Helendra (LP2M IAIN Ambon, 2025)
This study aims to analyze students' scientific argumentation skills in the context of environmental change using Toulmin's Argument Pattern. The topic of environmental change was selected due to its contemporary relevance and inherent complexity, which necessitates robust argumentation. The participants consisted of 76 Phase E (10th grade) students at SMAN 1 Koto XI Tarusan, selected through random sampling. A qualitative descriptive design was employed, with data collected through seven argumentative essay questions and student interviews. The responses were assessed using a rubric based on Toulmin’s components: claim, data, warrant, backing, and rebuttal. The findings revealed that 76% of students exhibited weak argumentation skills, 17% demonstrated moderate proficiency, and only 7% performed at a strong level. The study provides a comprehensive overview of students' argumentation abilities and identifies strengths and weaknesses in their application of Toulmin’s framework. The implications of this research highlight the need for developing more effective instructional strategies to enhance students' scientific argumentation skills, particularly in addressing environmental issues.